Tree preservation order in local authorities administration / Mohammad Fitry Md Wadzir - Md Wadzir, Mohammad Fitry (2019)
Tree is an essential source in our life in order to balance the human’s need and environmental aspect. Rapid development in urban area has caused maximum numbers of trees was cut this led to environmental issues. In Peninsular Malaysia, Tree Preservation Order (TPO) under Town and Country Planning Act 1976 has been created in order to protect the trees. Despite this way this kind of restriction is more beneficial towards the society, meanwhile it gives burden to the land owner as it gives unfavourably effect towards the value of land. Review of past studies shown that the studies focused on tree preservation’s benefit and less focusing on the landowner’s rights due as the restriction of Tree Preservation Order gives bad the effects toward the land value. This research aims to study the current standard operating procedure on the valuation of land compensation under Tree Preservation Order practicing by the local authorities. The objectives of this research are to identify the importance of tree preservation in local authorities’ administrative area in the stated of Perak, to determine the current practice applied by local authorities in identifying private alienated land to be gazette with tree preservation order and lastly to study the property owner rights against the tree preservation order. This research is based on data obtained from an interview of person in charge in the related department in three different local authorities in Perak.